Output Divergence in Fixed Exchange Rate Regimes: Is the Euro Area Growing Apart? - Yao Chen; Felix Ward (Tinbergen Institute, 2022)
Can fixed exchange rate regimes cause output divergence among member states? We show that such divergence is a long-run equilibrium characteristic of a two-region model with fixed exchange rates, heterogeneous labor markets, and endogenous growth. Under flexible exchange rates, monetary policy closes output gaps and realizes the associated maximum TFP growth in both regions. Upon fixing exchange rates, the region with higher structural wage inflation falls into a low-growth trap. When calibrated to the euro area, the model implies a slowdown in the TFP growth rate of the euro area\~As periphery relative to its core. An empirical analysis confirms that the periphery\~As higher structural wage inflation rate contributed to its lower TFP growth in the aftermath of joining the euro.
Keywords: E50; F31; O40; 330; Exchange rate; growth; monetary policy